Systematic controller design for digitally controlled LCL-type grid-connected inverter with grid-current-feedback active damping. (September 2019) - Zhu, Donghai; Zou, Xudong; Zhao, Yingying; Peng, Teng; Zhou, Shiying; Kang, Yong
Highlights: The system stability with grid current feedback active damping is analyzed. The stability criterions of control parameters are established. A systematic controller design method is proposed. Abstract: An LCL filter is commonly used in grid-connected inverter to attenuate the switching harmonics; nevertheless, the stability problems will arise in the grid current control if the resonance of LCL filter is not properly damped. High pass filter-based grid current feedback active damping is an effective solution to solve the aforesaid problem. However, for systems with digital control, the system may exhibit non-minimum phase system characteristics due to the control delay effect, which will affect the system stability. Moreover, the frequency responses of current controller parameters and active damping parameters are coupled. Therefore, to ensure the system stability and good dynamic performance, the current controller parameters and active damping parameters should be designed together, considering the control delay effect. For this issue, a systematic controller design method is proposed for the digitally controlled LCL -type grid-connected inverter with grid-current-feedback active damping. With the proposed method, the satisfactory regions of the control parameters for satisfying the system specifications can be obtained, from which the proper control parameters can be easily and quickly picked out, without the trial and error. Finally, the proposed design method is verified by the experiment.